Haul truck fuel consumption modeling under random operating conditions: A case study. (January 2022) - Golbasi, Onur; Kina, Elif
Abstract: This research study evaluates kinematic fuel consumption factors of haul trucks employed simultaneously in a multi-route operation network under stochastic payload and precipitation conditions. First, a discrete-event simulation algorithm was introduced, and significant parameters available in a material haulage system were correlated with time and location-based fuel usage behavior. Then, the model was validated with a large-scale cement production network covering two separate mines and one processing plant where fifteen different routes and twenty-nine trucks were available. The simulation results showed that precipitation conditions might lead to a variation in fuel consumption by 15–25 percent. Besides, the same-capacity trucks employed in the clay mine were detected to consume 40 percent more fuel in loaded travel than the limestone mine trucks due to the higher frequency of uphill loaded travels. The clay mine trucks also released 1.48 kg/km carbon dioxide in a complete production cycle, which is 17.5 percent more comparatively.